Membangun Kerukunan Umat Beragama Melalui Dialog Lintas Agama dan Budaya di Tengah Berbagai Tantangan di Indonesia - Dino Dino; Mayyadi Mayyadi (Jurnal Ilmu Sosial dan Humaniora, 2026)
Interfaith harmony is vital for the continuity of national life in Indonesia, a country characterized by religious, ethnic, and cultural diversity. This article examines the concept of interfaith harmony, the role of interfaith and intercultural dialogue in maintaining social harmony amidst contemporary challenges that hinder such harmony, and strategies that stakeholders can adopt to strengthen it. A descriptive-qualitative approach was employed, utilizing a literature review to analyze various scholarly works relevant to the topic. The analysis reveals that interfaith and intercultural dialogue—grounded in principles of equality, openness, honesty, and the acknowledgment of differences—effectively erodes prejudice, builds mutual trust, and prevents protracted interfaith conflicts. However, these efforts face serious challenges, including rising intolerance and radicalism, the exploitation of digital platforms to spread hoaxes and hate speech, the political manipulation of religious sentiment to secure power, and a lack of understanding regarding inclusive religious values ​​within certain social segments. Consequently, collaboration among the government, religious leaders, educational institutions, the public, and mass and social media is essential to sustain harmony. The article recommends strengthening the institutional capacity of the Interfaith Harmony Forum (FKUB), integrating religious moderation values ​​into educational curricula, and leveraging digital technology to extend the reach of tolerance-focused dialogue to the younger generation.